Inflammatory Myofibroblastic Tumour in Antimesenteric Border of Descending Colon of Children: A Case Report (Journal of Paediatric Surgeons of Bangladesh, 2015)
Inflammatory myofibroblastic tumour (IMT) occurring at intraabdominal sites in children has rarely been described. Inflammatory pseudotumour is a soft tissue lesion that may be confused with a sarcoma. It is abbreviated as IMT. Inflammatory myofibroblastic tumour, also known as soft tissue tumours, atypical fibromyxoid tumours, pseudosarcomatous fibromyxoid tumour, plasma cell granuloma, pseudosarcomatous myofibrotic proliferation, post-operative spindle cell nodules. In this paper, we describe a case of inflammatory myofibroblastic tumour (IMT) with an unusual constellation of clinical, pathological findings. A 10-year-old girl had an 7-cm intraabdominal mass accompanied by severe anemia, fever, constipation, weight loss, thrombocytosis, elevated erythrocyte sedimentation rate. Laparotomy was performed. The final pathologic diagnosis was IMT. At the most recent follow up (12months) after excision of the tumour, the patient was symptom-free and there was no evidence of tumour recurrence.J. Paediatr. Surg. Bangladesh 3(1): 47-50, 2012 (January)